Systems Analysis of a Maize Leaf Developmental Gradient Redefines the Current C-4 Model and Provides Candidates for Regulation - Pick, Thea R.; Braeutigam, Andrea; Schlüter, Urte; Denton, Alisandra K.; Colmsee, Christian; Scholz, Uwe; Fahnenstich, Holger; Pieruschka, Roland; Rascher, Uwe; Sonnewald, Uwe; Weber, Andreas P. M. (The Plant Cell, 2011)
We systematically analyzed a developmental gradient of the third maize (Zea mays) leaf from the point of emergence into the light to the tip in 10 continuous leaf slices to study organ development and physiological and biochemical functions. Transcriptome analysis, oxygen sensitivity of photosynthesis, and photosynthetic rate measurements showed that the maize leaf undergoes a sink-to-source transition without an intermediate phase of C-3 photosynthesis or operation of a photorespiratory carbon pump. Metabolome and transcriptome analysis, chlorophyll and protein measurements, as well as dry weight determination, showed continuous gradients for all analyzed items. The absence of binary on-off switches and regulons pointed to a morphogradient along the leaf as the determining factor of developmental stage. Analysis of transcription factors for differential expression along the leaf gradient defined a list of putative regulators orchestrating the sink-to-source transition and establishment of C-4 photosynthesis. Finally, transcriptome and metabolome analysis, as well as enzyme activity measurements, and absolute quantification of selected metabolites revised the current model of maize C-4 photosynthesis. All data sets are included within the publication to serve as a resource for maize leaf systems biology.